2021
DOI: 10.1038/s41596-021-00551-z
|View full text |Cite
|
Sign up to set email alerts
|

Using single-vesicle technologies to unravel the heterogeneity of extracellular vesicles

Abstract: Extracellular vesicles (EVs) are heterogeneous lipid containers with a complex molecular cargo comprising several populations with unique roles in biological processes. These vesicles are closely associated with specific physiological features, which makes them invaluable in the detection and monitoring of various diseases. EVs play a key role in pathophysiological processes by actively triggering genetic or metabolic responses. However, the heterogeneity of their structure and composition hinders their applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
125
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(149 citation statements)
references
References 255 publications
(440 reference statements)
1
125
0
Order By: Relevance
“…Extracellular vesicles (EVs) are nano- to micrometer-sized lipid membrane vesicles (mainly including exosomes and microvesicles) secreted by virtually all cell types ( 1 , 2 ). These vesicles are highly abundant in blood-derived plasma/serum, urine, cerebrospinal fluid (CSF), bile, saliva and other human biofluids ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Extracellular vesicles (EVs) are nano- to micrometer-sized lipid membrane vesicles (mainly including exosomes and microvesicles) secreted by virtually all cell types ( 1 , 2 ). These vesicles are highly abundant in blood-derived plasma/serum, urine, cerebrospinal fluid (CSF), bile, saliva and other human biofluids ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among the primary finding of our study, by applying a recently developed high‐throughput AFM‐based mechanical characterization method, which analyses the contact angle (a parameter related to the deformation extent) of a vesicle once adsorbed on a substrate, we demonstrated that small‐EVs derived from the two sources, bulk fluid ascites and tumor cells short‐term cultures, showed a markedly different stiffness. Compared to classical AFM‐based Force Spectroscopy (AFM‐FS), which represents one of the most widely used techniques for the mechanical characterization of lipid nanovesicles [ 49 ], the herein employed mechanical characterization allows obtaining information on vesicle mechanics just exploiting AFM imaging; this results in larger number of vesicles being sampled at the same time, together with a less challenging data analysis [ 50 , 51 , 52 ]. Moreover, in the original work, Ridolfi et al .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous reports have shown that cells secrete a heterogeneous population of EVs with different sizes and composition [ 30 , 31 ]. For example, EVs positive for CD63, a widely used exosome marker, represent only a fraction of EVs purified from dendritic or Hela cells [ 32 ].…”
Section: Discussionmentioning
confidence: 99%